Social Capital and Participation of Elderly Woman Based on the Sport Acceptance - Khodaparast , Siavash; Bakhshalipour , Vahid; Parsa, Abozar (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study was performed aiming to address the social capital and participation of elderly women based on the sport acceptance.Methods: The research method is applied and is a descriptive- survey research. The statistical population of the study includes the elderly women. 227 elderly women were selected as the sample size and simple probabilistic sampling method was used. Standard questionnaire was administered and SPSS and PLS were used for data analysis.Findings: The effect of cognitive social capital variable on the elderly women’s sport participation subjective development was 9.98, the effect of communication social capital on the subjective development of elderly was 2.71, the effect of structural social capital on the objective development of elderly women’s sport participation was 6.98 and effect of structural social capital on the subjective development of elderly women’s sport participation is 2.32 indicating that variables are influenced by each other. (p